Literature Review: The Role of Ascorbic Acid as a Priming Compound in the Physiological Response of Plants to Drought Stress - Nadhra, Muftia; Anggraini, Anggraini; Violita , Violita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Drought stress is a major abiotic factor that limits plant growth and productivity by disrupting photosynthesis, water uptake, and cellular metabolism. One strategy to enhance plant tolerance to drought is seed priming using ascorbic acid (AsA), which functions as an important antioxidant in plant defense systems. This study aims to systematically review the role of AsA as a priming compound in improving plant physiological responses under drought stress. A systematic literature review was conducted following the PRISMA framework. Relevant articles were collected from Google Scholar, ScienceDirect, and MDPI databases using keywords related to drought stress, seed priming, and ascorbic acid. Selected studies were analyzed descriptively to identify patterns of plant responses. The results indicate that AsA priming enhances antioxidant enzyme activities, reduces reactive oxygen species accumulation, maintains membrane stability, and improves germination, photosynthesis, and early seedling growth across several crop species. In conclusion, AsA seed priming is an effective approach to improve plant tolerance to drought stress. Future studies are recommended to explore optimal concentrations and molecular mechanisms of AsA application in different crop species.